Methods in Lexicography and Dictionary Research - Schierholz, Stefan J. (Lexikos, 2015)
Methods are used in every stage of dictionary-making and in every scientific analysis which is carried out in the field of dictionary research. This article presents some general considerations on methods in philosophy of science, gives an overview of many methods used in linguistics, in lexicography, dictionary research as well as of the areas these methods are applied in. Keywords: scientific methods; lexicographical methods; theory; metalexicography; dictionary research; practical lexicography; lexicographical process; systematic dictionary research; critical dictionary research; historical dictionary research; research on dictionary use